Fabrication and performance analysis of shell and tube heat exchanger system - Muhammad Izzat Aiman, Ahmad Padzil; Nurul Asyiqin, Rosli; Nadzirah, Mohd Mokhtar (2021)
The shell and tube heat exchangers (STHE) are still the most common type in uses. A typical STHE are built of round tubes mounted in a cylindrical shell with the tubes parallel to the shell. One fluid flow inside the tubes, while other fluid flows across the shell. STHE offer great flexibility to meet almost any service requirement.